Management of Salaf Islamic Boarding School in Improving the Quality of Students - Sakdiyah, Halimatus; Hamid, Abdul; Hayati, Nur (Al-Qalam Institue, 2025)
Salaf-based Islamic boarding schools in Indonesia face increasing pressure to modernize their management systems while maintaining their traditional religious identity. This research aims to describe the implementation of management at the Salaf-based Islamic boarding school in improving the quality of students at Pondok Pesantren Zainul Hasanain Genggong. The approach used is qualitative with a descriptive case study design, where data were obtained through interviews, observation, and documentation. The data were analyzed using thematic analysis techniques following the Miles and Huberman model to explore key themes in the application of traditional values in education. The research findings reveal that the management system in this Islamic boarding school is rooted in classical Islamic traditions, such as deliberative leadership (deliberation), moral exemplification by the kyai, and the yellow book learning model. These components collectively contribute to the development of students with strong religious character, self-discipline, and social awareness. However, challenges were found in the areas of limited professional management practices and infrastructure gaps. Despite this, the Islamic boarding school successfully fosters academic and non-academic excellence through structured guidance rooted in cultural-religious values. The implications of this research highlight the importance of value-based educational management that remains adaptive while preserving its identity within modern educational challenges.